The Reality Level of Feminism in Little Women Movie - Dinda, Putri; Dahniar, Dahniar; Tahir, Tahir (English Literature Studi Program Universitas Islam Makassar, 2023)
The research aims to identify and analyse the reality of feminism in the film Little Women. The problem identified in this study is to discover the signs of the level of feminism in the film Little Women. Furthermore, the research uses a qualitative descriptive method. The researcher downloaded